Tax avoidance - are banks any different? - Vanessa Gawehn; Jens Müller (Arbeitskreis Quantitative Steuerlehre (arqus), 2019)
While the public has noticed the need for the detection of potential tax loopholes and demand further improvement in the taxation of banks, there is scarce empirical evidence of whether banks' degree of tax avoidance actually differs from that of non-banks. We try to close this gap by investigating U.S. banks' tax avoidance behavior for a sample period from 2004 to 2016. To anchor banks' tax avoidance, we use annual Cash ETRs and GAAP ETRs and compare them to the tax avoidance behavior of non-banks. As there are various channels of tax avoidance, we account for differences in several areas such as corporate fundamentals, the degree of multinationality and regulatory scrutiny. We provide cautious evidence that banks have significantly larger Cash ETRs than non-banks. Via the use of quantile regression we find evidence that the assocation between banks and ETRs is not constant over the whole tax avoidance distribution, but shows a positive association for lower parts of the tax avoidance distribution and a negative association for higher parts. In line with recent research, we provide some evidence that the difference in Cash ETRs between banks and non-banks is more pronounced for worse-capitalized, than for better-capitalized banks.
Keywords: 330